Effects of Cytochrome P450 and Transporter Polymorphisms on the Bioavailability and Safety of Dutasteride and Tamsulosin - Villapalos-García, Gonzalo; Zubiaur, Pablo; Navares-Gómez, Marcos; Saiz-Rodríguez, Miriam; Mejía-Abril, Gina; Martín-Vílchez, Samuel; Román, Manuel; Ochoa, Dolores; Abad-Santos, Francisco (Frontiers in Pharmacology, 2021)
Dutasteride and tamsulosin are one of the first-line combination therapies for the management of benign prostatic hyperplasia (BPH). Despite being more effective than monotherapies, they produce frequent adverse drug reactions (ADRs). Institutions such as Food and Drug Administration and European Medicines Agency recommend precaution with CYP2D6 poor metabolizers (PMs) that receive CYP3A4 inhibitors and tamsulosin. However, no specific pharmacogenetic guideline exists for tamsulosin. Furthermore, to date, no pharmacogenetic information is available for dutasteride. Henceforth, we studied the pharmacokinetics and safety of dutasteride/tamsulosin 0.5 mg/0.4 mg capsules according to 76 polymorphisms in 17 candidate pharmacogenes. The study population comprised 70 healthy male volunteers enrolled in three bioequivalence, phase-I, crossover, open, randomized clinical trials with different study designs: the first was single-dose in fed-state, the second was a single-dose in fasting-state and the third was a multiple-dose. As key findings, CYP2D6 PMs and IMs presented higher AUC (p=0.004), higher t1/2 (p=0.008), and higher Cl/F (p=0.006) when compared with NMs and UMs after FDR correction. Moreover, fed volunteers showed significantly higher tmax than fasting individuals. Nominally significant associations were observed between dutasteride exposure and CYP3A4 and CYP3A5 genotype; and between tamsulosin and ABCG2, CYP3A5 and SLC22A1 genotypes. No association between the occurrence of adverse drug reactions and genotype was observed. Nonetheless, higher incidence of adverse events was found in multiple dose clinical trial. Based on our results, we suggest that dose adjustments for PMs or IMs could be considered to ensure drug safety and effectiveness, respectively. Further studies are warranted to confirm other pharmacogenetic associations.